#1**+2 **

Solve for r:

(r + 3)/(r - 2) = (r - 1)/(r + 1)

Cross multiply:

(r + 1) (r + 3) = (r - 2) (r - 1)

Expand out terms of the left hand side:

r^2 + 4 r + 3 = (r - 2) (r - 1)

Expand out terms of the right hand side:

r^2 + 4 r + 3 = r^2 - 3 r + 2

Subtract r^2 - 3 r + 2 from both sides:

7 r + 1 = 0

Subtract 1 from both sides:

7 r = -1

Divide both sides by 7:

** r = -1/7**

Guest Jun 10, 2019

#3**0 **

(r+3)/(r-2)=(r-1)(r+1)

(r+3)(r+1)=(r-1)(r-2)

r^2+4r+3=r^2-3r+2

7r=-1

r=-1/7

You are very welcome!

:P

CoolStuffYT Jun 10, 2019